The Strategy of the Sidoarjo Regency Cooperative office in Efforts to Develop the Competitiveness of Micro and Medium Enterprises - Isbahi, Surya Alimansyah; Fadil, Cholid; Imaningsih, Niniek (Pascasarjana Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency face various challenges in business development, particularly concerning product packaging and design. This study aims to enhance MSME owners’ understanding of product design and packaging, provide education on packaging selection strategies, and develop product competitiveness through attractive packaging designs. The method employed is a direct training approach, beginning with socialization through the Cooperative Office’s social media, participant selection, face-to-face training implementation, and post-activity evaluation. The training was attended by 30 selected MSME owners and czonducted on November 28, 2024, in the meeting room of the Sidoarjo Regency Industry and Trade Office. The training results indicate that participants have acquired basic knowledge about product packaging and design, although still limited to its fundamental functions. Participants also gained a deeper understanding of the importance of product taste consistency in building customer loyalty and facilitating business management. This activity makes a significant contribution to improving MSME owners’ knowledge of product packaging strategies and quality enhancement to increase competitiveness in the local market. For the future, it is expected that similar training can be held with a broader scope of materials and reach more MSME owners